Phenological changes reflect climate change in Wisconsin - Bradley, Nina L. (The National Academy of Sciences, 1999)
A phenological study of springtime events was made over a 61-year period at one site in southern Wisconsin. The records over this long period show that several phenological events have been increasing in earliness; we discuss evidence indicating that these changes reflect climate change. The mean of regressions for the 55 phenophases studied was −0.12 day per year, an overall increase in phenological earliness at this site during the period. Some phenophases have not increased in earliness, as would be expected for phenophases that are regulated by photoperiod or by a physiological signal other than local temperature.